Penalaran Wacana Argumentatif Mahasiswa Perbandingan Madzhab dan Hukum (Pmh) - Rahmiati, Rahmiati (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2016)
This study aims to find patterns and techniques of reasoning in students’ argumentative written discourse in an effort to cultivate critical thinking among the students majoring in Comparative Schools of Islamic Jurisprudence and Law (PMH) State Islamic University of Alauddin Makassar. To achieve these objectives, the approach used in this study was a qualitative approach with a theoretical orientation discourse analysis. The research data were the written discourse obtained from the assignment of students to write argumenttative discourse. Data were analyzed using three basic steps, namely data reduction, data presentation, and drawing conclusions. The results indicate that the students’ patterns of reasoning in argumentative written discourse in their effort to cultivate critical thinking among students can be grouped into four patterns, namely: (1) pattern CGB, (2) pattern CGWB, (3) pattern CGB-MQ, and (4) pattern CGWB-MQ. In addition, the students’ reasoning techniques in writing argumentative discourse include: (1) the argument with examples, (2) the argument with the authority, and (3) the argument with causes.